2020
DOI: 10.35848/1347-4065/ab840e
|View full text |Cite
|
Sign up to set email alerts
|

Development of optical resolution photoacoustic microscopy with sub-micron lateral resolution for visualization of cells and their structures

Abstract: Photoacoustic (PA) imaging is a hybrid imaging technique with light-dependent contrast and ultrasound-dependent depth. In previous studies, the interest of PA imaging was mainly clinical research. However, in recent years, PA imaging that targets cells also has attracted attention. Cells are the smallest unit in our body, and cell abnormalities cause various diseases. Therefore, PA imaging of cells is important for elucidating the relationship between diseases and PA properties and linking the results to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It uses tightly focused laser irradiation with a much smaller focus area than that of the acoustic reception beam. As a result, OR-PAM has achieved an optical-dependent high lateral resolution of 0.2–10 µm with a penetration depth of up to 1 mm 20 24 , furthermore its high resolution indicates the potential to perform (1) clinical imaging of capillaries and their metabolic activity, (2) preclinical imaging of small animals such as mice 21 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It uses tightly focused laser irradiation with a much smaller focus area than that of the acoustic reception beam. As a result, OR-PAM has achieved an optical-dependent high lateral resolution of 0.2–10 µm with a penetration depth of up to 1 mm 20 24 , furthermore its high resolution indicates the potential to perform (1) clinical imaging of capillaries and their metabolic activity, (2) preclinical imaging of small animals such as mice 21 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the photoacoustic measurement can reach the diameters down to 0.1 mm order by employing high power pulsed laser source and 10 MHzorder ultrasound transducer array. An attempt to give optical resolution to photoacoustic microscopy was reported [31]. Photoacoustic tomography of vascular compliance was also studied [32].…”
Section: Introductionmentioning
confidence: 99%
“…Different from the imaging-based phase-delay thoughts, the authors have investigated the relationship between the excitation pulse width and the acoustic resonance inside a tube [31,32]. The acoustic resonance is caused by a light pulse, and then monitored as photoacoustically induced ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the photoacoustic effect, biomedical imaging technology like photoacoustic microscopy (PAM), photoacoustic tomography (PAT) and photoacoustic endoscope (PAE) has developed rapidly. [11][12][13][14] The photoacoustic effect has also been used to make optoacoustic transducers. [15][16][17][18][19][20] This kind of transducer can generate high-frequency ultrasound (>50 MHz) while achieving element size and spacing on the order of several microns.…”
mentioning
confidence: 99%